The heterogenicity of Cowdria ruminantium stocks: cross-immunity and serology in sheep and pathogenicity to mice - Du Plessis, J L; Van Gas, L; Olivier, J A; Bezuidenhout, J D (Onderstepoort journal of veterinary research, 1989)
Ten stocks of Cowdria ruminantium (Ball 3, Breed, Comoro, Germishuys, Kümm, Kwanyanga, Mali, Mara, Nonile and Welgevonden) were compared from a cross-immunity, serological and mouse pathogenicity point of view. They were found to differ in varying degrees. Except for the Ball 3, Comoro and Germishuys stocks that were similar but not identical, there was no pattern in the antigenic diversity of the 10 stocks. The Welgevonden stock emerged as the stock that elicits an immunity against most of the South African stocks. The inability of the reference Ball 3 stock to protect sheep against no fewer than 6 other stocks questions the advisability of retaining this stock as the vaccine stock. The antigenic diversity of the 10 stocks could not be correlated with the antibody levels detected with the indirect fluorescent antibody test, since the sera against all 10 stocks reacted positively to the Kümm stock antigen and the variation in titres was not stock-related.